Poverty Alleviation through Sociocultural Education Programs to Improve The Social Welfare of The Community - Farouq, Mgs. Muhammad; Kriyantono, Rachmat; Hakim, Muhammad Lukman; Sahiruddin, S (Universitas Muhammadiyah Surakarta, 2024)
Poverty is still widely found in Indonesia, especially in rural areas. The relatively low level of education of rural communities results in a lack of community contribution to pursue welfare. There are still many rural people who do not have jobs in the area where they live. On the other hand, some regions in Indonesia are very advanced and developed which are not far from the countryside. This is a phenomenon that is quite concerning. This study examines the impact of the